2015
DOI: 10.1021/acs.est.5b03377
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Formation and Evolution of Individual Compounds in the Particulate Phase during Aromatic Photo-Oxidation

Abstract: 1Secondary organic aerosol (SOA) is well known to have adverse effects on air quality and 2 human health. However, the dynamic mechanisms occurring during SOA formation and 3 evolution are poorly understood. The time resolved SOA composition formed during the 4 photo-oxidation of three aromatic compounds, methyl chavicol, toluene and 4-methyl 5 catechol, were investigated at the European Photo-reactor. SOA was collected using a particle 6 into liquid sampler and analysed offline using state-of-the-art mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 89 publications
(196 reference statements)
0
26
0
Order By: Relevance
“…The relative low volatility of N-containing products could reasonably contribute to SOA formation (Duporté et al, 2016;. In addition, a higher NO 2 /NO ratio favors the formation of nitro-substituted products, which are potentially involved in NPF and SOA growth (Pereira et al, 2015). Ng et al (2007a) also indicated that NO x could be beneficial to SOA formation for sesquiterpenes due to the formation of low-volatility organic nitrates and the isomerization of large alkoxy radicals, resulting in less volatile products.…”
Section: Effect Of No 2 On Soa Formationmentioning
confidence: 99%
“…The relative low volatility of N-containing products could reasonably contribute to SOA formation (Duporté et al, 2016;. In addition, a higher NO 2 /NO ratio favors the formation of nitro-substituted products, which are potentially involved in NPF and SOA growth (Pereira et al, 2015). Ng et al (2007a) also indicated that NO x could be beneficial to SOA formation for sesquiterpenes due to the formation of low-volatility organic nitrates and the isomerization of large alkoxy radicals, resulting in less volatile products.…”
Section: Effect Of No 2 On Soa Formationmentioning
confidence: 99%
“…Wang et al: Observations of fine particulate nitrated phenols aerosols (SOAs; Pereira et al, 2015). Via photo-oxidation and aqueous-phase reactions, nitrated phenols could alter the tropospheric photochemistry and influence SOA formation, thus affecting regional air quality and atmospheric visibility (Mohr et al, 2013;Laskin et al, 2015;Chow et al, 2016;Yuan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Via photo-oxidation and aqueous-phase reactions, nitrated phenols could alter the tropospheric photochemistry and influence SOA formation, thus affecting regional air quality and atmospheric visibility (Mohr et al, 2013;Laskin et al, 2015;Chow et al, 2016;Yuan et al, 2016). In addition, nitrated phenols are hazardous to plants, animals, aquatic life, and humans (Natangelo et al, 1999;Schüssler and Nitschke, 2001;Harrison et al, 2005a;Ganranoo et al, 2010). The significant roles of nitrated phenols in the atmosphere and their adverse effects on living things have triggered the need to understand their pollution characteristics and their origins.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, C 8 H 7 NO 4 and C 9 H 9 NO 4 from BB emissions are more stable and are supposed to have a phenyl cyanate structure. Among the four NAC formulas with MW > 200 Da identified in this work (Table 2), C 10 H 11 NO 4 was also observed as 5-methoxy-4-nitro-2-(prop-2-en-1-yl)phenol in SOA from reactions of methyl chavicol and NO x (Pereira et al, 2015), which cannot be assigned to the C 10 H 11 NO 4 from BB emissions in this work. Compared to the NACs in aromatic VOCs and NO x SOA (Iinuma et al, 2010;Lin et al, 2015;Xie et al, 2017a;Pereira et al, 2015), the structures of NACs from BB in this work were characterized by methoxy and cyanate groups.…”
Section: Identification and Quantification Of Nacsmentioning
confidence: 60%